Outcomes of Immune Thrombotic Thrombocytopenic Purpura (iTTP) With Upfront Cyclophosphamide vs. Rituximab - Abou-Ismail, Mouhamed Yazan; Arafah, Yasmin; Fu, Pingfu; Cao, Shufen; Schmaier, Alvin H.; Nayak, Lalitha (Frontiers in Medicine, 2020)
Background: Immune thrombotic thrombocytopenic purpura (iTTP) is a rare, life-threatening disorder managed with plasma exchange (PLEX) and steroids. Addition of rituximab (RTX) to initial disease treatment has been shown to lower future relapse rates. Information as to whether upfront cyclophosphamide (CTX) treatment is helpful in reducing relapse is not known. Methods: In a retrospective cohort study, we identified all patients at our institution diagnosed with iTTP between 2010 and 2019. We analyzed outcomes of cumulative incidence of relapse (CIR) and duration of remission. Results: Thirty Nine patients were studied. Group A (n = 10) included patients who received upfront PLEX and steroids alone, and Group B (n = 28) included those who received either upfront RTX (n = 23) or CTX (n = 5) in addition to PLEX and steroids. The 2-year CIR was 50% in Group A and 27.7% in Group B, with a median duration of remission of 43.6 months vs. 108.3 months, respectively (p = 0.04). Group A was associated with a HR=8.7 (95% CI: 1.27, 59.45), p = 0.027 for duration of remission. There was no significant difference between CTX and RTX in both outcomes of CIR and duration of remission. We observed a potential impact on remission duration based on the presenting absolute neutrophil count (HR = 0.74, 95% CI: 0.58, 0.96) and serum creatinine (HR = 1.42, 95% CI: 1.03, 1.94). Conclusion: There was no significant difference in iTTP relapse outcomes between upfront RTX and CTX. Absolute neutrophil count and serum creatinine may have a role in predicting relapse. Larger, prospective studies are needed to evaluate these findings.